Strategic and Potential Analysis of Tourism Village – Based Economic Development Through Flagship Halal Products in Aceh Province - Bulan, Tengku Putri Lindung; Chandra, Riny; Amilia, Suri; Mardhani, Martahadi (Institut Teknologi dan Bisnis Asia Malang, 2025)
This study conducts an in-depth analysis of strategies and potentials for developing the local economy through flagship halal products in tourist villages in Langsa City, Aceh Province. The research provides factual data on local potential, products, and their management, along with recommended strategies to enhance the role of tourist villages in improving the community’s economy. A descriptive qualitative approach was employed, using interviews with relevant government agencies and village officials, baseline surveys in two tourist villages across different sub-districts, and Focus Group Discussions (FGDs) to validate survey findings and assess the quantity and quality of flagship halal products. The data were analyzed using the TOWS method, structured within a discussion framework to derive comprehensive conclusions. The novelty of this study lies in its methodological approach and focus on flagship halal products as a backbone of the village economy. The findings highlight that strengthening integrated halal tourism packages—by combining culinary and handicraft products with tourist attractions, enhancing digital marketing outreach, and empowering village cooperatives as economic institutions is essential to increasing tourist interest and accelerating local economic growth.